PENGARUH CONTENT MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK ARTISAN PROFESSIONNEL - Meilyana (2022)
This study uses quantitative methods with the aim of proving the influence of content marketing and electronic word of a local cosmetic product called Artisan Professional. Data collection was carried out by researchers through the distribution of questionnaires via Google form. This study uses 100 respondents from Artisan Professional consumers who live in Central Jakarta as primary data, and secondary data researchers obtain through various references related to the research. The sampling technique uses non-probability sampling with the purposive sampling method. The media for distributing the questionnaires were chosen by the researchers via Instagram, WhatsApp, the Official Artisan Professional Website, and Twitter. In analyzing, researchers used descriptive and inferential analysis techniques which were processed through SmartPLS 3.0. So data processing obtains the results that (1) content marketing has a significant positive effect on purchasing decisions, (2) electronic word of mouth has a significant positive effect on purchasing decisions.